THE EFFECTIVENESS OF THE COOPERATIVE INTEGRATED COMPOSITION MODEL ON THE LEARNING OUTCOMES OF THE VIII GRADE STUDENTS OF MTs AL MANAR MEDAN PERIOD OF 2017/2018 - Tuti Alawiyah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to determine the effectiveness of the cooperative integrated composition model on the learning outcomes of the VIII grade students of MTs Al Manar Medan TA 2017/2018. This study uses a total sample of students in class VIII1 as the experimental group and class VIII2 as a control group. Each group consists of 35 students. This study uses a quasi-experimental method, with the instrument of learning outcomes Fiqh Halal and Haram food and beverage material in the form of objective multiple choice questions as many as 30 questions. This test was tested after each group was treated using a cooperative and conventional integrated composition learning model. To find out the effectiveness of the cooperative integrated composition model, the calculations using the t test are performed. Based on the data analysis technique, the results of the study are as follows: Fiqh learning outcomes of students on Halal and Haram Food and Beverage material taught using the cooperative integrated composition learning model have an average value of average 74.2. Student Fiqh learning outcomes on Halal and Haram food and beverage material taught using conventional learning models has an average value of 69. Statistically using the t-test it is concluded that the cooperative integrated learning model of learning is effectively used in improving the learning outcomes of students in Fiqh class VIII MTs Al Manar Medan TA 2017/2018. This is evidenced from the results of hypothesis testing where tcount> ttable is 2,271> 1,668. Keywords : Students, Fiqih, Islamic Shool (Madrasah)